Planning and Design of Airports, Fifth Edition - Horonjeff, Robert; McKelvey, Francis; Sproule, William; Young, Seth (McGraw-Hill Education, 2010)
Fully updated to reflect the significant changes that have occurred in the aviation industry, the new edition of this classic text offers definitive guidance on every aspect of planning, design, engineering, and renovating airports and terminals. Planning and Design of Airports, Fifth Edition, includes complete coverage of the latest aircraft and air traffic management technologies, passenger processing technologies, computer-based analytical and design models, new guidelines for estimating required runway lengths and pavement thicknesses, current Federal Aviation Administration (FAA) and International Civil Aviation Organization (ICAO) standards, and more.